Pemaafan (Forgiveness) Istri Terhadap Suami Pelaku Pelecehan Seksual pada Anak - Fauzia Ramadhianty; Harry Theozard Fikri (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
The purpose of this study is to find out how the forgiveness of the wife (forgiveness) of the husband of the perpetrators of sexual abuse of children. The subjects of this study were two wives whose husbands were sexually abusing children. The research method used in this study is a qualitative research method with a phenomenological research design. Based on research by researchers carefully that two subjects forgive their husbands who sexually abuse children. In this study there are three aspects of forgiveness, namely 1) avoidance motivations, 2) revenge motivations, and 3) beneviolence motivations. From the research findings on both subjects, it was found that the aspects that caused forgiveness in both subjects were avoidance motivations, and beneviolence motivations. While from the aspect of revenge motivations, it is not the cause of the two subjects giving forgiveness to their husbands, because the feelings of love and love of the subject to their husbands are not what they used to be, and they choose to stay with their husbands because of their children and in-laws.